3D quantitative analysis of graphite morphology in high strength cast iron by high-energy X-ray tomography. (September 2015) - Chuang, Chihpin; Singh, Dileep; Kenesei, Peter; Almer, Jonathan; Hryn, John; Huff, Richard
Abstract :   The size and morphology of the graphite particles play a crucial role in determining various mechanical and thermal properties of cast iron. In the present study, we utilized high-energy synchrotron X-ray tomography to perform quantitative 3D-characterization of the distribution of graphite particles in high-strength compacted graphite iron (CGI). The size, shape, and spatial connectivity of graphite were examined. The analysis reveals that the compacted graphite can grow with a coral-tree-like morphology and span several hundred microns in the iron matrix.